Exploration of the association between the single-nucleotide polymorphism of co-stimulatory system and rheumatoid arthritis - Chen, Ding-Ping; Wen, Ying-Hao; Lin, Wei-Tzu; Hsu, Fang-Ping; Yu, Kuang-Hui (Frontiers in Immunology, 2023)
The human leukocyte antigen (HLA) has been linked to the majority of autoimmune diseases (ADs). However, non-HLA genes may be risk factors for ADs. A number of genes encoding proteins involved in regulating T-cell and B-cell function have been identified as rheumatoid arthritis (RA) susceptibility genes. In this study, we investigated the association between RA and single nucleotide polymorphisms (SNPs) of co-stimulatory or co-inhibitory molecules in 124 RA cases and 100 healthy controls without immune-related diseases (including TNFSF4, CD28, CTLA4, and PDCD1). The results showed that there were 13 SNPs associated with RA, including rs181758110 of TNFSF4 (CC vs. CT, p = 0.038), rs3181096 of CD28 (TT vs. CC + CT, p = 0.035; CC vs. TT, p = 0.047), rs11571315 (TT vs. CT, p = 0.045), rs733618 (CC vs. TT + CT, p = 0.043), rs4553808 (AA vs. AG vs. GG, p = 0.035), rs11571316 (GG vs. AG vs. AA, p = 0.048; GG vs. AG + AA, p = 0.026; GG vs. AG, p = 0.014), rs16840252 (CC vs. CT vs. TT, p = 0.007; CC vs. CT, p = 0.011), rs5742909 (CC vs. CT vs. TT, p = 0.040), and rs11571319 of CTLA4 (GG vs. AG vs. AA, p < 0.001; GG vs. AG + AA, p = 0.048; AA vs. GG + AG, p = 0.001; GG vs. AA, p = 0.008; GG vs. AG, p = <0.001), rs10204525 (TT vs. CT + CC, p = 0.024; TT vs. CT, p = 0.021), rs2227982 (AA vs. GG, p = 0.047), rs36084323 (TT vs. CT vs. CC, p = 0.022; TT vs. CT + CC, p = 0.013; CC vs. TT + CT, p = 0.048; TT vs. CC, p = 0.008), and rs5839828 of PDCD1 (DEL vs. DEL/G vs. GG, p = 0.014; DEL vs. DEL/G + GG, p = 0.014; GG vs. DEL + DEL/G, p = 0.025; DEL vs. GG, p = 0.007). Consequently, these SNPs may play an important role in immune regulation, and further research into the role of these SNPs of immune regulatory genes in the pathogenesis of RA is required.